The Late Medieval Image Debate in English and French Literature, 1160-1500 : Constructive Iconoclasm - Ni, Yun, (Late Antiquity and Medieval Studies E-Books Online, Collection 2025., 2026)
Early modern reformers claimed to reject a superstitious, image-obsessed medieval past-but what if medieval thinkers had already begun to critique sacred images? This book reveals how late medieval literature reimagined breaking images as radical creation, not destruction. Step into the world of Arthurian legends, The Romance of the Rose , and saints' lives, where shattered statues and broken relics generate new meaning. Explore the writings of Chaucer and Julian of Norwich, who grapple with divine truth not by preserving images, but by dismantling and remaking them. This book uncovers a literary self that is dynamic, assertive, and subversive centuries before the Renaissance claims to invent it.